Investigation on the Effect of Centrifugation Speed on the Shape Separation of Gold Nanorods - Minun, Caessandra Addine; Anâ€™Nisa, Nur Zehan; Morsin, Marlia; Razali, Nur Liyana; Nafisah, Suratun; Sanudin, Rahmat; Salleh, Muhamad Mat (International Journal of Engineering and Technology, 2018)
High-quality gold nanorods (AuNRs) with a uniform aspect ratio and sizes are crucial for applications in biomedical or sensor industry. AuNRs is implementing Localized Surface Plasmon Resonance (LSPR) as sensing method which is highly dependent on the size, separation of nanoparticles, aspect ratio and the shape of the nanoparticles. Thus, in this process, the shape, surface density and aspect ratio of AuNRs were investigated to be used further as LSPR sensing material. The AuNRs was prepared using Seed Mediated Growth Method (SMGM) and the growth solution of the AuNRs was centrifuged with the speed ranging from 2500 rpm to 5000 rpm to separate the particles shaper prior to deposition as thin film. The XRD result shows the peak at 2Î¸ = 38Âº which shows the (111) crystal orientation of the AuNRs. There are also two distinct peaks formed at the absorption spectra graph obtained from the UV-Vis result which associated with transverse plasmon peak (t-LSPR) and longitudinal plasmon peak (l-LSPR). The t-LSPR peak is significantly smaller than the l-LSPR and located in the wavelength ranges from 500 nm to 560 nm whereas the l-LSPR of the AuNRs shows a stronger and a higher peak which is located in the wavelength ranges from 700 nm to 780 nm. The morphological analysis using FESEM shows that the higher centrifugation speed separates the AuNRs with higher aspect ratio and higher surface density.